The evaluation of European criminal law: the example of the Framework Decision on combating trafficking in human beings - Weyembergh, Anne; Santamaria, Veronica (Editions de l’Université de Bruxelles, 2009)
The role of evaluation has become increasingly important in the context of EU policies in the field of judicial cooperation in criminal matters. This evolution is the result of an increasing number of legally binding instruments adopted in the framework of the third pillar of the European Union and of their growing impact on national legal systems